Biological Invasions in the South American Anthropocene: Global Causes and Local Impacts - Castro-Morales, S (Springer International Publishing, 2021)
This book provides a conceptually organized framework to understand the phenomenon of biological invasions at the Anthropocene global scale. Most advances toward that aim have been provided from North American and European researchers, with fewer contributions from Australia and South Africa. Here we fill the void from the Neotropics, focusing on the research experience in South American countries, with a strong emphasis on Argentina and Chile. © Springer Nature Switzerland AG 2021. All rights reserved.